THE RELATIONSHIP OF SOCIAL SUPPORT WITH THE EVENT OF DEPRESSION POSTPARTUM - Hafsah Hafsah; Subki Subki; Myrna Lestari; Ernita Ernita (Universitas Karya Husada Semarang, 2024)
Women are prone to experiencing depression, especially in the postpartum phase. The postpartum period refers to the postpartum phase, where the reproductive organs and body systems undergo the process of returning to their pre-pregnancy form. This period begins immediately after the baby is born and lasts up to 6 weeks (40 days). This study aims to determine the relationship between social support and postpartum events. This research uses a quantitative research design with cross sectional techniques. The research focused on postpartum mothers who lived in the Mainland Work Area Health Center, North Aceh Regency. The sample was determined using a simple random sampling method, namely 60 respondents using the Slovin formula. The results of the research show that there is a relationship between social support (p-value 0.001<0.05) and the incidence of postnatal depression in the Pasir Tanah Community Health Center working area.